A Content Analysis of Current Issues in Supply Chain Management - Mohd Rizaimy Shaharudin; Nik Ramli Nik Abdul Rashid; Chutima Wangbenmad; Chattrarat Hotrawaisaya; Preecha Wararatchai (International Journal of Supply Chain Management, 2018)
This paper presents a content analysis to review and offer the latest study of literature in supply chain management (SCM). The SCM literature seems to require a review study on a regular basis to keep updated on the changes of its dynamic and complex characteristics. Drawing from the 58 articles from Emerald Insight and Science Direct databases, this study provides an appropriate analysis from the four pre-identified keywords to explore the recent articles published in the years 2016 and 2017, as well as the issues that have been revisited for further analysis. The results revealed five prime issues and four major scopes that have become the focus of the recent study, which suggests the future research propositions in SCM.